2004
DOI: 10.1007/s00428-004-1127-9
|View full text |Cite
|
Sign up to set email alerts
|

P16INK4a expression and progression risk of low-grade intraepithelial neoplasia of the cervix uteri

Abstract: The aim of the study was to evaluate the immunohistochemical expression of p16INK4a as a marker of progression risk in low-grade dysplastic lesions of the cervix uteri. p16INK4a immunohistochemistry was performed on 32 CIN1 with proven spontaneous regression of the lesion in the follow-up (group A), 31 (group B) with progression to CIN3 and 33 (group C) that were randomly chosen irrespective of the natural history of the lesion. p16INK4a staining pattern was scored as negative (less than 5% cells in the lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
92
0
9

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(106 citation statements)
references
References 24 publications
5
92
0
9
Order By: Relevance
“…One prospective study of women with CIN 1 demonstrated a higher rate of regression of p16 INK4A -negative CIN 1 lesions (71%) compared to p16-positive CIN 1 lesions (38%). 20 Although some p16-negative CIN 1 lesions progressed to CIN 3 in that study, the p16-positive lesions were much more likely to progress. Another prospective study demonstrated that 44% of women with p16 INK4A -positive biopsies that were classified as ''not CIN 2,3'' by consensus pathology were subsequently diagnosed with CIN 2,3.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…One prospective study of women with CIN 1 demonstrated a higher rate of regression of p16 INK4A -negative CIN 1 lesions (71%) compared to p16-positive CIN 1 lesions (38%). 20 Although some p16-negative CIN 1 lesions progressed to CIN 3 in that study, the p16-positive lesions were much more likely to progress. Another prospective study demonstrated that 44% of women with p16 INK4A -positive biopsies that were classified as ''not CIN 2,3'' by consensus pathology were subsequently diagnosed with CIN 2,3.…”
mentioning
confidence: 64%
“…23 Moreover, women with cervical biopsies that are p16 INK4a -positive but not diagnosed as CIN 2,3 are at greatly elevated risk for subsequently being diagnosed with CIN 2,3 and women with p16 INK4a -negative CIN 1 lesions are less likely to progress to CIN 3 than those with p16 INK4a -positive CIN 1. 16,20 Numbers do not add up to totals due to missing data and are as shown. Cases of invasive cervical cancer are not included.-2 v 2 test for trend except for median RLU value that is by Kruskall-Wallace test.-3 P0 is ''warrants colposcopy'' diagnosis.- 4 If high-risk HPV DNA positive by hc2, RLU is relative light units that is an indicator of HPV DNA content or viral load.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Other studies analyze specific groups, which were retrospectively selected based on the outcome. 17,27 Independently of their design, all these studies show that patients with LSIL/CIN1 with diffuse p16 staining are at higher risk of progression to HSIL/CIN2-3 and suggest the need for closer follow-up. 5,16,17,25,26 However, all these studies reported a relative inaccuracy of p16 to predict the outcome of LSIL/CIN1, thereby questioning the usefulness of follow-up strategies modulated by p16.…”
Section: Discussionmentioning
confidence: 99%
“…17,27 Independently of their design, all these studies show that patients with LSIL/CIN1 with diffuse p16 staining are at higher risk of progression to HSIL/CIN2-3 and suggest the need for closer follow-up. 5,16,17,25,26 However, all these studies reported a relative inaccuracy of p16 to predict the outcome of LSIL/CIN1, thereby questioning the usefulness of follow-up strategies modulated by p16. 5,22,26 The main strength of our study is that it includes a large series of women with LSIL/CIN1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation